ANALISIS PENDIDIKAN KARAKTER GEMAR MEMBACA DALAM KULTUR SEKOLAH DASAR NEGERI 46 KOTA SINGKAWANG - Sumiati Sumiati; Sulistyarini Sulistyarini; Agung Hartoyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThis study aims to describe the analysis of character education for reading fondness in the culture of Singkawang Public School 46. This research is a descriptive study with a qualitative approach. The subjects of this study were principals, teachers and participants in SD Negeri 46 Kota Singkawang. The data was collected by observing, interviewing and documenting. Data analysis was carried out in stages: data reduction, data display, and drawing conclusions. Data validity checking techniques using technical triangulation and data source triangulation. The results showed that the analysis of character education for reading fondness in elementary school culture was as follows: (1) the planning was that the teacher had included the character of reading fondness in the lesson plan, the components in the lesson plan were in accordance with the existing guidelines (2) in practice the students had perform activities related to the character who likes reading. (3) in the evaluation of the results of the teacher, assessing the attitudes of students, namely the attitude of characters who like reading. (4) the obstacles faced are that students' reading interest is still lacking or not very enthusiastic, then there are still limited facilities and infrastructure that support reading activities.Keywords: Character Analysis, Love to Read, In Elementary School Culture